Criteria for Research Productivity Grants in Brazil Applied to Civil Engineering: Reflections on Gender Differences and the Current Context - LILIAN R. DE REZENDE; VERÔNICA T.F. CASTELO BRANCO; KAMILLA V. SAVASINI; MARTA P. DA LUZ; MICHÉLE D.T. CASAGRANDE; LISEANE P. THIVES; LÊDA C.F.L. LUCENA; LIEDI L.B. BERNUCCI (Anais da Academia Brasileira de Ciências)
Abstract This article addresses gender issues in the context of the professor’s productivity grants (PQ) distribution applied to Civil Engineering. It contributes with reflections on the advancement of knowledge and gender equality through the inclusion of integrity and holistic aspects. A quantitative and descriptive data analysis of public documents revealed that the number of women civil engineers is considerable, and that female professors engaged in postgraduate are capable of competing for scholarships. Nevertheless, less than 20% of PQ scholarships are awarded to female civil engineers, and the current scenario point to a gender disparity in terms of approval PQ demands. Moreover, despite the majority having already reached the pinnacle of their academic careers, only one has been designated at the highest level, and none have attained the rank of Senior. These findings can indicate segregation, structural barriers, lack of support and policies that encourage access to the highest levels of scholarships, possible subjectivity in the judgment that lead to the lack of impartiality and discrimination, and other factors that may still be understood as gender discrimination. Thus, the PQ criteria can be reviewed in light of the Brazilian National Care Policy, Sustainable Development Goal 5, and gender mainstreaming.